Improving the Ability to Write Observation Report Texts through the Application of the Problem Based Learning Model - Okta Shelty; Yessi Fitriani; Puspa Indah Utami (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aimed to enhance Grade X students’ observation report writing skills and learning activities at SMA Negeri 1 Tungkal Jaya by implementing Problem Based Learning (PBL). A Classroom Action Research (CAR) design was employed, conducted over two cycles, each comprising planning, implementation, observation, and reflection. Data were analyzed using descriptive statistical techniques. Results demonstrated significant improvement. Students achieving the mastery score (≥70) increased from 37% (Cycle I) to 87% (Cycle II), representing a 38.89% skill enhancement. The class average rose from 75.60 to 85.00. Polite learning behaviors improved from 56% to 90%. All assessed aspects showed gains, with language and creativity exhibiting the highest increases. The study provides empirical, cycle-based evidence for applying PBL specifically to observation report writing, a foundational academic genre, within a local Indonesian high school context. Findings strongly support adopting PBL as an effective pedagogical strategy for improving both the product (writing skills) and process (classroom engagement) of learning in similar educational settings. The research contributes actionable insights to educational practice, validating PBL’s role in fostering active learning and significantly improving specific compositional competencies among secondary school students.